Is The Value of FDG PET/CT in Evaluating Renal Metastasis Underestimated? A Case Report and Review of The Literature - (:unkn) unknown (My University, 2013)
Contrast-enhanced CT or MRI are used as a gold standard imaging modalities in the detection and characterization of renal masses. On the other hand, the role of FDG PET/CT in evaluating primary or metastatic cancers of the kidney is limited due to the excretion of FDG through urinary tract. We reported the FDG PET/CT of a lung cancer patient with multiple metastases in both kidneys which were missed in previous PET/CT, and underestimated on sequential diagnostic abdominal CT study. CONFLICT OF INTEREST: None declared.
Keywords: Akciğer tümörleri; bilgisayarlı tomografi; böbrek tümörleri; fluorodeoksiglukoz F18; pozitron emisyon tomografi